Rodas em redes geográficas: os caminhos devocionais das caravanas de São Francisco das Chagas de Canindé – CE - Silva, Ivo Luis Oliveira (2019)
This thesis presents the objective of unveiling the movement-image of the pilgrims' caravans in the Canindé Sanctuary; present the meanings, meanings, social interactions, symbolic, imaginary and tourist constructions; to contemplate the effects of the caravan hybridization from the suspension of the macaw wood and the re-edition of the caravans with the tourist charter and eventual. The methodology used is the ethnographic method complemented with informal interviews, simple observations and participants, documentary and bibliographic research. The chosen place is the Sanctuary of São Francisco das Chagas de Canindé, in the state of Ceará. In the field, the symbolic discourse of the penitent medievalist projection of “who goes to Canindé! It goes to suffer”. For the purposes of analysis, the implications between tradition and postmodern society; the landscape and the symbolic character of the backlands; the technical rationality of the public agents and the tourist and eventual charters; of the duality between the “impurity” of the tourist pilgrimage and the “purity” of the penitent pilgrimage. Imagination returns to the certainty that travel has achieved a cultural preference for the holy place, a radiance with the traveling message of the place, and a pilgrim religiosity that fits postmodernity.